The theology of John Duns Scotus - Vos, A. (Studies in Reformed Theology, 2018)
In this volume, Antonie Vos offers a comprehensive analysis of the philosophy and theological thought of John Duns Scotus. First, a summary is given of the life and times of John Duns Scotus: his background and years in Oxford (12-80-1301), his time in Paris and Cologne (1308-1309) and his year in exile in Oxford and Cambridge (1303-1304). From there on, Scotus' Trinitarian theology and Christology are introduced. Duns not only embraced the doctrine of the Trinity, he also proved that God must be Trinitarian by connecting the first Person with knowledge to the second One with will. Further insights of Scotus' are discussed, such as the theory of Creation, ethics, justification and predestination, and the sacraments. The volume concludes with an overview of historical dilemmas in Scotus' theological thought.